New Zealand policy experts’ appraisal of interventions to reduce smoking in young adults: a qualitative investigation - Janet Hoek; Heather Gifford; Jude Ball; El Shadan Tautolo (BMJ Open)
Objectives Reducing smoking in young adults, particularly young Māori and Pacific, is vital for reducing tobacco harm and health inequalities in New Zealand (NZ). We investigated how NZ policy experts appraised the feasibility and likely effectiveness of interventions designed to reduce smoking prevalence among 18–24 year olds.Design We used a qualitative design, conducting semistructured interviews and applying thematic analysis.Participants We interviewed 15 key informants, including politicians, senior policy analysts and leading tobacco control advocates. Participant selection was based on seniority and expertise and ensuring diverse perspectives were represented.Interventions We examined nine interventions that could either promote greater mindfulness or introduce barriers impeding smoking uptake: smoke-free outdoor dining and bars; no tobacco sales where alcohol is sold; social marketing campaigns; real life stories (testimonials); life skills training; raise purchase age to 21; tobacco-free generation; smokers’ licence; make tobacco retail premises R18.Results The policies perceived as more effective denormalised tobacco; made it less convenient to access and use; highlighted immediate disadvantages (eg, impact on fitness); aligned with young people’s values; and addressed the underlying causes of smoking (eg, stress). Participants highlighted some political barriers and noted concerns that some interventions might widen ethnic disparities. Exceptions were social marketing campaigns and extending smoke-free regulations to include outdoor areas of cafes and bars, which participants saw as politically feasible and likely to be effective.Conclusions Our findings suggest the merit of an approach that combines social marketing with regulation that makes accessing and using tobacco less convenient for young adults; however, political barriers may limit the regulatory options available in the short term. Strategies to support self-determination and address the underlying causes of smoking in young people warrant further investigation. Determining policy acceptability to Māori and Pacific, and likely effectiveness for these populations, should be key priorities.